Clinical insights of pregnancy management, adrenal insufficiency as a possible cause of elevated TSH: a pilot study of case series - Ken Kanazawa; Tatsuro Inaba; Shinichiro Koga; Koichiro Kuwabara (BMC Pregnancy and Childbirth, 2023)
Abstract Background The upper limit for thyroid-stimulating hormone has been strictly defined for pregnancy management, at which point levothyroxine replacement therapy will been initiated. However, it is essential to exclude adrenal insufficiency, including subclinical adrenal insufficiency, when initiating levothyroxine replacement therapy. However, in pregnancy management, it has rarely reported the incidence, clinical course, and characteristics of adrenal insufficiency as a possible cause of elevated thyroid-stimulating hormone. Methods This case series study included pregnant patients undergoing thyroid-stimulating hormone management in a single-center diabetes endocrinology department between 2017 and 2020. The primary study outcome was the incidence of newly diagnosed adrenal insufficiency. We reported the clinical course and assessed the adrenal insufficiency characteristics at baseline and delivery and compared them with those of hypothyroidism. Result Fifteen pregnant women were included for thyroid-stimulating hormone management; and nine were below the basal serum cortisol level, and four were newly diagnosed as having adrenal insufficiency (26.7%) with the endocrinological stimulation test. Among them, two cases exhibited nausea and hypoglycemic symptoms after the start of levothyroxine replacement therapy. In cases of adrenal insufficiency, the patients were successfully treated with appropriate steroid coverage. Conclusions In the management of elevated thyroid-stimulating hormone levels during pregnancy, the frequency of adrenal insufficiency suspecting hypothyroidism may be higher than expected; therefore, we must be careful about starting levothyroxine replacement therapy for hypothyroidism. These clinical insights can have a significant impact on the pregnancy outcomes.